The Role of a Nurse in The Management of Material: An Integrative Review - Ashi, Rangappa. S.; Deshpande, Prasanna; Patil, Vidyashree. (Research & Review: Management of Emergency and Trauma Nursing (e-ISSN: 2582-0494), 2022)
The object of the study is the operation of medical- sanitarium inventories. This is an area that requires the health care workers to have specific knowledge and which has presently sparked conversations among experts on the subject.